2015
DOI: 10.1136/bjophthalmol-2015-306628
|View full text |Cite
|
Sign up to set email alerts
|

Radius of curvature changes in spontaneous improvement of foveoschisis in highly myopic eyes

Abstract: Background Myopic foveoschisis is the splitting of retinal layers overlying staphyloma in highly myopic patients that can lead to vision loss. We assess possible contributing mechanisms to the formation of foveoschisis by examining two cases of spontaneous improvement of myopic foveoschisis and employ a radius of curvature (ROC) measure to track posterior scleral curvature over time. Methods A retrospective, non-comparative case series was performed and optical coherence tomography images were analysed. Reti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 32 publications
0
22
0
Order By: Relevance
“…Quantitative analysis of fundus shape would lead not only to a better understanding of the pathogenesis of staphyloma but also to prediction of its development and progression, as well as give an indication of the prognosis for vision-threatening myopic retinopathies in each patient with high myopia at risk. Previous studies have attempted quantitative analysis of the association between staphyloma and myopic retinopathy by measuring the depth of staphyloma using B-scan ultrasonography 31 , measuring staphyloma depth using OCT 17 , measuring best-fit radius of curvature 32 , or classifying posterior staphyloma 18 . However, grading of B-scan ultrasonography is not suitable for detailed analysis of staphyloma.…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative analysis of fundus shape would lead not only to a better understanding of the pathogenesis of staphyloma but also to prediction of its development and progression, as well as give an indication of the prognosis for vision-threatening myopic retinopathies in each patient with high myopia at risk. Previous studies have attempted quantitative analysis of the association between staphyloma and myopic retinopathy by measuring the depth of staphyloma using B-scan ultrasonography 31 , measuring staphyloma depth using OCT 17 , measuring best-fit radius of curvature 32 , or classifying posterior staphyloma 18 . However, grading of B-scan ultrasonography is not suitable for detailed analysis of staphyloma.…”
Section: Discussionmentioning
confidence: 99%
“…Some patients with severe forms of tractional changes were reported to have a higher risk for progression to FRD, full-thickness MH, and MHRD, which may result in acute substantial visual impairment. [36][37][38] In such patients, early detection and timely surgical intervention could effectively improve their visual acuity and quality of life. Given that the development of MTM has similar important clinical significance, and clinics are now using OCT routinely, a traction component should be considered as a possible component to the myopic macular classification.…”
Section: This Study Is To the Best Of Our Knowledge The Firstmentioning
confidence: 99%
“…We believe that the advantage of sclera imbrication is that it does not require surgical procedures around the macula. In contrast, Hoang and associates [27] reported that the curvature radius of the posterior sclera was reduced after a spontaneous resolution of a macular retinoschisis in highly myopic eyes. They assumed that the decrease of the tractional force from the ILM, vitreous cortex, and staphyloma may be related to the reduced curvature radius of the posterior sclera.…”
Section: Discussionmentioning
confidence: 96%